Dye-sensitized Pt@TiO2 core–shell nanostructures for the efficient photocatalytic generation of hydrogen - Cao, Shao-Wen (2014)
Pt@TiO2 core–shell nanostructures were prepared through a hydrothermal method. The dye-sensitization of these Pt@TiO2 core–shell structures allows for a high photocatalytic activity for the generation of hydrogen from proton reduction under visible-light irradiation. When the dyes and TiO2 were co-excited through the combination of two irradiation beams with different wavelengths, a synergic effect was observed, which led to a greatly enhanced H2 generation yield. This is attributed to the rational spatial distribution of the three components (dye, TiO2, Pt), and the vectored transport of photogenerated electrons from the dye to the Pt particles via the TiO2 particle bridge.